Red Tape and Community Workers’ Proactive Behavior During COVID-19: Applying the Job Demands–Resources Model - Hu, Wei; Zhang, Shengjie; Liu, Songbo (Frontiers in Psychology, 2022)
Applying the job demands–resources model, this study demonstrates how red tape affects proactive behavior and explores the role of lack of goal progress and public service motivation. In order to measure the variables in the model accurately, we used a two-wave survey with different emphases in Beijing, China. After matching the responses from the two waves, our sample included a total of 656 community workers who completed questionnaires. We found a negative relationship between red tape and proactive behavior, while lack of goal progress mediates the direct relationship. Contrary to our hypothesis, public service motivation did not moderate the relationship between lack of goal progress and proactive behavior. These findings have important theoretical and practical implications and will better inform community work during COVID-19.